TOPIC: PERSONAL AND MENTAL DEVELOPMENT OF A CHILD AT DIFFERENT AGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is about child development. That is, in the personal, mental, social development of the child, there is a reflection on what the parents pay attention to and the physical and, conversely, the invisible, that is, the internal changes in the child.